2013
DOI: 10.7314/apjcp.2013.14.10.6103
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Repair Gene ERCC6 rs1917799 Polymorphism is Associated with Gastric Cancer Risk in Chinese

Abstract: Objective: Excision repair cross-complementing group 6 (ERCC6) is a major component of the nucleotide excision repair pathway that plays an important role in maintaining genomic stability and integrity. Several recent studies suggested a link of ERCC6 polymorphisms with susceptibility to various cancers. However, the relation of ERCC6 polymorphism with gastric cancer (GC) risk remains elusive. In this sex-and age-matched case-control study including 402 GC cases and 804 cancer-free controls, we aimed to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
13
0
2
Order By: Relevance
“…The results for ERCC2 rs50871 was opposite to the previous findings in melanoma [25] or head and neck cancer [26], in which the GG genotype was related to favorable survival. ERCC6 rs1917799 was previously linked to increased risk of GC [27], but its role in GC prognosis has not been studied before. In this study, ERCC6 rs1917799 heterozygote GT was firstly found to be associated with significantly shorter OS than wild-type TT.…”
Section: Discussionmentioning
confidence: 99%
“…The results for ERCC2 rs50871 was opposite to the previous findings in melanoma [25] or head and neck cancer [26], in which the GG genotype was related to favorable survival. ERCC6 rs1917799 was previously linked to increased risk of GC [27], but its role in GC prognosis has not been studied before. In this study, ERCC6 rs1917799 heterozygote GT was firstly found to be associated with significantly shorter OS than wild-type TT.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous pilot study, three potential functional SNPs, ERCC6 rs1917799, ERCC8 rs158572 and rs158916 were detected and two of them were supposed to be associated with GC risk [10, 11]. In the current study, we further analyzed the interaction effect of the SNPs, and found that ERCC6 rs1917799 and ERCC8 rs158572 polymorphisms were associated with CAG and GC.…”
Section: Discussionmentioning
confidence: 71%
“…Population-based epidemiologic studies have shown that ERCC6 and ERCC8 polymorphisms have a significant impact on the risk of some human malignancies, including gastric cancer [10, 11, 16, 2830]. In vitro evidence indicated that ERCC6 polymorphisms may alter protein function [16, 31], and reduced ERCC6 protein levels were associated with increased cancer risk [32, 33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is individual susceptibility to GC even with the same environmental exposure. Genetic factors, including variants in genes involved in the pathogenesis of GC :http://dx.doi.org/10.7314/APJCP.2014.15.6.2863 The 765G>C Polymorphism andGastric Cancer Risk-a Meta-analysis may contribute to these differences (Goto et al, 2005;Shibata et al, 2010;Sethi et al, 2012;Liu et al, 2013;Chen et al, 2014;Li et al, 2014). Therefore, during the past 10 years, genetic susceptibility evoked researchers' interest, and studies concerning polymorphisms of genes involved in the pathogenesis of GC are expanding each year.…”
Section: Discussionmentioning
confidence: 99%